Urban tree planting should consider local characteristics: assessing spatial heterogeneity in canopy cooling effects on land surface temperature using Bayesian spatially varying coefficient models. - Ruiz-Valero, Ángel; Pereña-Ortiz, Jaime Francisco; Salvo-Tierra, Ángel Enrique (Frontiers, 2025)
Urban trees are essential for mitigating elevated temperatures in cities worldwide, with many municipalities implementing large-scale urban tree planting initiatives. However, the cooling potential of tree canopy coverage is often estimated as a constant value across study areas, despite evidence that temperature reductions depend on local characteristics, including tree traits and urban geometry.
Keywords: Árboles de ciudad; Ecología urbana; Flora urbana; Cubierta arbórea; Bioestadística; Urban ecology; Urban forestry